Reflections on plague in African history (14th–19th c.) - Gérard Chouin (Afriques)
In 1347, the western and Mediterranean parts of the Old World recorded the first outbreaks of a returning mortal disease that would make its presence felt over several centuries. Known today as the Second Plague Pandemic—a zoonosis due to the bacterium Yersinia pestis—it scythed between a third and half of the population without regard for wealth or status. It deeply transformed all facets of societies, ignited fears, violence, and pogroms, tested the flexibility of religions, hierarchies, and traditions, and excited ambitions. Although the plague is commonly described as a pandemic, historical knowledge about the initial Black Death and the many recurrent waves of the disease is largely restricted to Western Europe and the Mediterranean world, where the literate elite left an impressive documentary record that served as resource to the long-lasting and flourishing heuristic tradition of Plague Studies. If, as suggested by Monica Green, the concept of ‘pandemic’ is to be taken seriously, we must consider the many excluded parts of the Old World, and especially Africa, in our plague narratives. We must recognize that these societies that did not practise ‘the reduction of speech to graphic forms’—to use the expression coined by Jack Goody—also could have experienced the brutal mortality of the plague and its radical transformative power, while producing no organized and specific, long-lasting traces. By extension, we must also recognize that all literate societies that had in common the art of writing did not practise this art in the same way and may not have produced identical categories of documentary records. Cultural differences affect the nature of the documentary archive, as illustrated by literate practices in medieval Nubia and Ethiopia. The invisibility or limited visibility of the plague in the documentary record is, therefore, a challenge for historians and a disguised invitation to accept the absence of evidence as evidence of absence. This paper is my attempt to resist this temptation, to challenge the quasi-absence of interest in the plague problem in the historiography of Sub-Saharan Africa, and to lay out the foundation of a research strategy that will be multi-disciplinary and comparative. The plague problem is not a footnote to African history. If the plague impacted African societies as it did in documented parts of the Old World, we must have missed or misread fundamental processes of change it entailed. Would we understand and interpret the history of Western Europe or the Mediterranean as we do if we ignored that the plague had occurred? Here, I do not solve the plague conundrum in Sub-Saharan Africa; rather, I build on the persuasive arguments made by other contributors to this special issue about the presence of plague in different parts of Africa before the 19th century. My purpose is to propose multiple, critical, and cumulative—but far from exhaustive—pathways to reading and rereading the traditional and less traditional sources of African history in the light of the possibility of societal crises related to plague. Besides presenting fragments of evidence, this paper also serves as an introduction to three groundbreaking papers exploring the archaeological, documentary, and genomic sources of the disease in the African past.